Volatile Solvent Abuse among Street Children and Adolescent in India: A Systematic Review - Sevak, Sanjay; Lal, Sudershna (Innovational: Journal of Nursing and Healthcare, 2024)
In India, the previous few decades have been a period of rapid increase in consumption of substance abuse. Recently, volatile solvent is comparatively recent phenomenon among street children, urban youth, and adolescence. Volatile solvent is deliberate inhalation of fumes and petroleum derivatives for euphoria and mind-altering effects. The impact of volatile solvents substance also occurs rapidly and disappears reasonably quickly, compared with other types of substance abuse. The volatile solvent abuser has a significant impact on physical, mental, social, psychological, and economical area of individual life. The reasons for volatile solvents attract street children and adolescents because of easy availability, low price, poor impulse control, and peer pressure. The adverse consequence of volatile abuse affects not only the individual user but also the whole family and society. Management of volatile solvent abuse includes treatment as well as prevention. The treatment incorporates many components including behavior therapy, psychotherapy, pharmacotherapy, social support, and awareness. Hence, it is necessary to provide health education, mass media educational activities, and health promotion programs directed toward street children and their families. It will help to improve the knowledge among adolescents to comply with ill effects of volatile solvent abuse and to continue with healthy living. At the same time, public awareness about volatile solvent abuse and its associated risks awareness need to be raised. This review mainly focuses on the current status of volatile solvent abuse, risk factors, associated factors, prevalence, complication, and recommendations, which may help the youth and family to understand prevalence and allied serious problems.